Crohn’s Disease with Comorbidites of Syndrome of Inappropriate Anti Diuretic Hormone (SIADH) caused by Pulmonary Tuberculosis - Steven, Rios; Miro, Saptino; ., Arnelis; Yoga, Vesri; Viotra, Deka; Elvira, Dwitya; ., Wahyudi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Crohn's disease is an inflammatory condition of the intestines characterized by lesions that can affect the entire digestive tract from the mouth to the anus. Globally, the prevalence of inflammatory bowel disease has increased over the past 20 years, rising from 3.32 million cases in 1990 to 4.9 million cases in 2019. Previously, the management of Crohn’s disease followed the step-up therapy approach; however, this method led to higher recurrence rates. The current approach utilizes top-down therapy, as research data indicate that the remission rate is 57% with top-down therapy compared to 25% with step-up therapy. Syndrome of Inappropriate Antidiuretic Hormone (SIADH) can be caused by pulmonary tuberculosis. A 44-year-old male patient was diagnosed with Crohn’s disease based on a colonoscopy examination, which suggested chronic active colitis with mild activity and crypt distortion consistent with Crohn’s disease. An esophagogastroduodenoscopy (EGD) revealed chronic gastritis, while a histopathological examination of the colon confirmed findings consistent with Crohn’s disease. The diagnosis of pulmonary tuberculosis was established using a rapid molecular test (TCM) with positive results. Hyponatremia with hypoosmolar euvolemia was diagnosed based on serum sodium levels of 128 mmol/L, serum osmolality of 269 mosmol/L, urine osmolality of 288 mosmol/L, and urine sodium of 73 mosmol/L. Treatment included 5-ASA and anti-tuberculosis medications. Crohn’s disease increases morbidity rates and is not limited to developing countries. It is caused by immune system dysregulation, which can predispose patients to secondary infections such as tuberculosis. Pulmonary tuberculosis, in turn, can lead to SIADH.Keywords: Crohn’s disease, pulmonary tuberculosis, SIADHTop of Form